Pengukuran Efisiensi Alokatif pada Usaha Pertanaman Kacang Tanah di Kecamatan Sambung Makmur, Kabupaten Banjar - Sadik Ikhsan (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The research aimed to examine allocative efficiency of available inputs or factor of production utilization in peanut farming in the Sub-district of Sambung Makmur, the Dictrict of Banjar, South Kalimantan using a Cobb-Douglas production function approach. The estimation of Cobb-Douglas production function was, however, carried out by applying procedures of principal component regression instead of well-known OLS regression due to multicollinearity problems. The results revealed that all inputs significantly influenced peanut production. Nevertheles, some inputs such as chemical pesticides and hired labour had negative elasticity of production indicated that those were over-utilized and, therefore, not consistent with maximizing profit. There were perhaps increasing pest attacks in the observed planting time so that farmers needed more pesticides to employ. Besides, farmers need more hired labour to substitute shortage of family labor. From statistical test of allocative efficiency indeces showed that land and fertilizer were allocatively efficient, whereas seeds and family labor were not yet due to under-utilized. In order to attain maximizing profit, it was suggested to increase the use of seeds and family labor. Less utilization of family labor was in fact consistent with more utilization of hired labor because the latter was needed to substitute lack of the former.